Clinical in‐vivo dosimetry for total skin electron therapy using gafchromic™ EBT4 film - Zhexuan Zhang; Lan Lu; Gregory M. M Videtic; Cherian Sheen; Ping Xia; Peng Qi (Journal of Applied Clinical Medical Physics, 2026)
Abstract Background Total skin electron therapy (TSET) is a standard treatment for cutaneous T‐cell lymphoma. Due to the complex patient positioning and irregular body contours, robust in‐vivo dosimetry (IVD) is essential to verify dose uniformity. While thermoluminescent dosimeters (TLDs) are traditional standard, their utility is hindered by labor‐intensive, manual processing. Purposes This study evaluates the clinical implementation of a Gafchromic™ EBT4 film‐based IVD system integrated with a bespoke, open‐source analysis platform for automated batch‐processing. To address the inherent orientation dependence and loss of film orientation frequently encountered when preparing small‐format IVD films with a manual paper cutter, we developed an orthogonal dual‐scan protocol. By averaging pixel values from two perpendicular scans for both calibration and clinical measurement, this protocol effectively mitigates orientation‐dependent uncertainties and ensures dosimetric robustness. Methods The film‐based IVD system was clinically assessed in five TSET treatments and compared to six treatments utilizing TLD‐based IVD. Dosimetric accuracy was evaluated by comparing normalized fractional doses to the prescription. Statistical analysis was performed using the Mann‐Whitney U test with the Benjamini‐Hochberg procedure to control the false discovery rate across 20 anatomical sites. Workflow efficiency was quantified by the total time required for data readout and analysis per patient. Results The EBT4 film‐based IVD demonstrated dosimetric accuracy comparable to the TLDs, with mean fractional doses of 102.7% ± 9.6% and 100.4% ± 9.7%, respectively ( p = 0.25). Clinical implementation of the film‐based approach significantly enhanced efficiency, reducing the total processing time from approximately 50 min to 15 min per treatment. Conclusions The proposed EBT4 film‐based IVD system, supported by open‐source software and an orthogonal dual‐scan protocol, offers a robust, cost‐effective, and time‐efficient alternative to traditional TLDs. This approach streamlines the clinical workflow without compromising dosimetric accuracy, making it a viable solution for TSET and broader radiotherapy IVD applications.